The value of tolerance in learning Nusantara dance - Sofa, Tresna Maya (FBSB UNY, 2023)
Tolerance is an attitude that must be owned by every individual as part of the diversity of the world community, especially as citizens of Indonesia with various ethnicities, cultures, languages, and customs. Archipelago Dance Learning is one of the subjects that can instill the value of tolerance in students. In the cognitive domain, students learn various dances, both dance as physical, ideas, and systems. Meanwhile, in affection, students learn to appreciate, appreciate, and love various types of dance in Indonesia. In the psychomotor domain, students learn to practice the movements of the Nusantara Dance. This paper will examine the role of learning Indonesian dance towards the tolerance attitude of students through a hermeneutic approach. This study uses a qualitative descriptive method with a Gadamer hermeneutic approach to gain the broadest possible understanding of the learning of Nusantara Dance in instilling tolerance values in students. The results obtained from this study indicate that based on the results of analysis and interpretation, the results show that learning Indonesian dances not only provides theoretical knowledge about the diversity of traditional dances in Indonesia but also becomes a medium for instilling tolerance values in students. Understanding various cultures and understanding the various customs, norms, and values of certain ethnic groups or ethnic groups.Keywords: tolerance, multiculture, learning archipelago dance Nilai toleransi pada pembelajaran Tari NusantaraAbstrakToleransi merupakan salah satu sikap yang harus dimiliki oleh setiap individu sebagai bagian dari keberagaman masyarakat dunia, terlebih sebagai warga negara Indonesia yang beraneka ragam suku bangsa, budaya, bahasa, dan adat istiadat. Pembelajaran Tari Nusantara merupakan salah satu mata pelajaran yang mampu menanamkan nilai toleransi bagi peserta didik. Pada ranah kognitif peserta didik mempelajari bebagai tari yang ada baik tari sebagai fisik, ide maupun sistem. Sementara ranah afeksi peserta didik belajar mnegapresiasi, menghargai , dan mencintai berbagai macam tari di Indonesia. Pada ranah psikomotorik peserta didik belajar mempraktikan gerak-gerak Tari Nusantara. Tulisan ini akan mengkaji peranan pembelajaran Tari Nusantara terhadap sikap toleransi peserta didik melalui pendekatan hermeneutik. Penelitian ini menggunakan metode deskripsi kualitatif dengan pendekatan hermeneutic Gadamer untuk mendapatkan pemahaman seluas mungkin mengenai pembelajaran Tari Nusantara dalam menanamkan nilai toleransi pada peserta didik. Adapun hasil yang diperoleh dari penelitian ini menunjukan bahwa Berdasarkan hasil analisis dan penafsiran diperoleh hasil bahwa pembelajaran tari nusantara tidak hanya memberikan pengetahuan secara teori mengenai keberagaman tari tradisi yang ada di Indonesia tetapi juga menjadi media dalam menanamkan nilai toleransi bagi peserta didik. Memahami ragam budaya dan turut memahami beragam adat istiadat, norma, dan nilai pada kelompok etnis atau suku bangsa tertentu.Kata Kunci: toleransi, multikultural, pembelajaran tari nusantara